Інформаційні ризики при роботі з віртуальним середовищем - Шульга, М. Д. (ХНУРЕ, 2023)
As the adoption of virtualization technologies grows, it attracts more attention from potential attackers. Issues such as data leaks, breaches in isolation, and insecure configurations can restrict flexibility and heighten risks linked to specific vulnerabilities. Identifying and addressing these risks help maintain the confidentiality, integrity, and availability of data in the virtual environment. Thus, early detection of information security risks bolsters risk management strategies.